The cross-cultural adaptation of Chinese international students in Malaysia: a systematic review - Zhao, Wenwen; Osman, Mohd Nizam; Omar, Siti Zobidah; Yaakup, Hani Salwah (Universiti Sultan Zainal Abidin, 2023)
With the accelerating process of globalisation, studying abroad has gradually become a common phenomenon. China is the world's largest source of international students, and Chinese students’ adaptation to a foreign country has always been the focus of scholars. Although Chinese students have become the second-largest group of international students in Malaysia, few studies concentrated on the cross-cultural adaptation of this group in Malaysia. This literature review further confirms this situation. From 2010 to 2021, only 14 articles were obtained through both Google Scholar and Scopus databases and manual search. Among the limited literature,4 articles took Chinese international students as samples. In other research, the samples were international students from all over the world, and Chinese students only accounted for a part. Moreover, most of the studies only selected samples from one location, affecting the results' representative. In addition, the research topic was relatively unitary; the 14 studies mainly discussed the factors affecting the cross-cultural adaptation of Chinese students in Malaysia and suggested suggestions to improve their adaptation. In terms of research design, 12 articles applied a cross-sectional survey but onlyinvolved independent and dependent variables without moderating or mediating variables; the research framework was relatively simple. However, cross-sectional studies cannot determine causal relationships between variables and are insufficient to show the dynamic process of cross-cultural adaptation. On this basis, some suggestions for future research are put forward.